Hubungan antara Pengaruh Teman Sebaya, Kebiasaan Makan di Luar (Eating Out), dan Pola Konsumsi Fast Food dengan Status Gizi Lebih Remaja di SMAN 1 Surabaya - Janice Fiona Putri; Dini Ririn Andrias (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Adolescents are considered a vulnerable group to nutritional problems because they experience rapid physical growth accompanied by lifestyle changes and unhealthy eating habits. The increasing prevalence of overweight and obesity among teenagers has become a major public health concern that requires serious attention. This study was conducted to examine the relationship between peer influence, the frequency of eating out, and fast-food consumption habits with the incidence of overweight among students at SMAN 1 Surabaya. The research applied a quantitative approach using an analytical observational design with a cross-sectional method. A total of 81 students participated in the study and were selected through proportional random sampling. Data were collected using questionnaires, SQ-FFQ forms, and anthropometric measurements, then analyzed using the Chi-Square statistical test. The findings revealed significant associations between peer influence, eating out frequency, and fast-food consumption habits with the occurrence of overweight among adolescents. Students who more frequently consumed meals outside the home and regularly ate fast food showed a greater tendency to experience overweight and obesity. These results indicate that social environments and modern dietary patterns contribute to the increasing prevalence of overweight among adolescents. Therefore, nutrition education and healthy lifestyle promotion should be strengthened through the involvement of schools, families, and peer groups.